PENANAMAN NILAI KARAKTER MELALUI EKSTRAKURIKULER SENI MUSIK ANGKLUNG DI SDN 4 GUBUG KABUPATEN GROBOGAN - Alfina Harubi Wijayanti; Sunan Baedowi; Mira Azizah (Universitas Ngudi Waluyo, 2022)
The COVID-19 pandemic has caused various impacts in the world of education, especially the character degradation that has occurred in elementary school students. This phenomenon is accompanied by a character lost effect caused by the learning transition. Based on this background, it is necessary to make efforts to replant character values in students. SD Negeri 4 Gubug has an innovative concept to overcome these problems by launching angklung music extracurricular activities. The focus of this research is to analyze the inculcation of character values through extracurricular activities of angklung music. The method used is descriptive qualitative. The research data were taken by using observation, interview, and documentation techniques. The research subjects were extracurricular students, extracurricular supervisors, and the principal of SD Negeri 4 Gubug. The results showed that there were character values that were realized, including religious values, discipline, responsibility, social care, environmental care, friendly/communicative, independent, and love for the homeland. The obstacles that occur are the absence of a special room, and the limited number of angklungs. While the existing support includes material support in the form of facilities and moral support from the school.